2019
DOI: 10.1177/2378023119886406
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Theories of Resource Distribution: The Case of Iran

Abstract: This study addresses inequality through resource distribution in Iranian provinces with the use of new data collected and compiled from various sources using multilevel modeling. The models compare predictions of the various resource distribution theories using Iran’s 31 provincial budgets over 10 years. This resource distribution study provides a rare look at inequality in a country that, to a large degree, prohibits such examinations. The authors find that although ethnicity, religiosity, and allegiance to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…However, the above-cited studies did not consider some important criteria reported in Table 2, such as "Human Resources" and "Flexibility and Technical Capability", leaving their analysis incomplete. Moreover, none of the produced studies trying to prioritize the R&M method considered the Iranian context (Amani et al, 2012(Amani et al, , 2013Motamed & Majrouhi, 2018), which is featured by highly constrained and unequally distributed resources (Ledford & Lynch, 2019). In this regard, as demonstrated by Vanier et al (2006) in their study aimed at comparing different prioritization techniques, the R&M method to use highly depends on the assigned weight of factors made by evaluators, which vary by culture and organizational need.…”
Section: Maintenance Based On the Situationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the above-cited studies did not consider some important criteria reported in Table 2, such as "Human Resources" and "Flexibility and Technical Capability", leaving their analysis incomplete. Moreover, none of the produced studies trying to prioritize the R&M method considered the Iranian context (Amani et al, 2012(Amani et al, , 2013Motamed & Majrouhi, 2018), which is featured by highly constrained and unequally distributed resources (Ledford & Lynch, 2019). In this regard, as demonstrated by Vanier et al (2006) in their study aimed at comparing different prioritization techniques, the R&M method to use highly depends on the assigned weight of factors made by evaluators, which vary by culture and organizational need.…”
Section: Maintenance Based On the Situationmentioning
confidence: 99%
“…However, the above-cited studies did not consider some important criteria, such as "Human Resources" and "Flexibility and Technical Capability", nor did they consider the case of Iran, showcased by highly constrained and unequally distributed resources (Ledford & Lynch, 2019). In this context, other studies tried elaborating tools for easing maintenance management of facilities in Iran (Amani et al, 2012(Amani et al, , 2013Motamed & Majrouhi, 2018), but, no-one aimed at prioritizing the criteria for selecting appropriate R&M methods for CBs.…”
Section: Introductionmentioning
confidence: 99%
“…Access to financial institutions is resolved by creating conditions for independent smallholders from all branches of the financial industry (SIIA, 2018). Unequal allocation and access to resources are resolved by resource distribution with budgets and geographic proximity (Ledford & Lynch, 2019).…”
Section: The Sustainable Standard Toward the Benefit Of Sustainable D...mentioning
confidence: 99%
“…On the other hand, the previous research studies did not consider some important criteria, such as "Human resources" and "Flexibility and technical capability (FTC)" as well as they did not consider the case of developing countries (e.g. Iran), featured by constrained and unequally distributed resources (Ledford and Lynch, 2019). In this contextual regard, other studies tried elaborating tools for facilitating maintenance management of facilities F 40,5/6 (Amani et al, 2013;Motamed and Majrouhi, 2018), but no one aimed at prioritizing the essential criteria for selecting appropriate R&M methods of CREs.…”
Section: Introductionmentioning
confidence: 99%